2018
DOI: 10.7759/cureus.2913
|View full text |Cite
|
Sign up to set email alerts
|

Violence among Adolescents in Qatar: Results from the Global School-based Student Health Survey, 2011

Abstract: BackgroundDespite being a neglected issue in adolescent health, interpersonal violence such as physical fighting constitutes a prominent cause of physical injuries in adolescents.AimWe aimed to study the prevalence of physical fighting and its associated factors among Qatar's adolescent population.MethodWe analyzed secondary data from Qatar's Global School-based Student Health Survey (GSHS) 2011 to determine the prevalence as well as the associated factors of being engaged in a physical fight in the last 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Supportive parents were found to be protective of physical fights as observed in other studies in Ghana, Namibia, and Chile [9,28,38] though not in studies from the Caribbean and Malaysia were no association was noted [3,22]. On the other hand, supportive parents were found to have an increased risk among males but protective among females in Qatar [25]. This study measured parental support through how often parents checked the homework of adolescents.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Supportive parents were found to be protective of physical fights as observed in other studies in Ghana, Namibia, and Chile [9,28,38] though not in studies from the Caribbean and Malaysia were no association was noted [3,22]. On the other hand, supportive parents were found to have an increased risk among males but protective among females in Qatar [25]. This study measured parental support through how often parents checked the homework of adolescents.…”
Section: Discussionmentioning
confidence: 65%
“…Studies conducted in the East Mediterranean region have shown the prevalence to range from 46% to 65% among males, 21% to 48% among females, and from 41% to 58% among both sexes [1,15]. Compared to high income countries, the prevalence is lower compared to studies conducted in Israel and Qatar each at 49%, UAE at 43% [15,24,25]; Portugal at 34% and the US at 31% and 36% [15,26,27] though higher compared to other studies conducted in Europe and North America ranging from 9-14% [28,29]. Students involved in physical fights were more likely to be males, involved in bullying victimization, planned suicide, and missed school, while understanding parents and being physically inactive were found to be protective.…”
Section: Discussionmentioning
confidence: 99%
“…Bala et al, studied the prevalence of physical fighting and its associated factors among the adolescent population in Qatar [ 18 ]. This study was based on a student health survey in school to determine the prevalence and factors associated with being engaged in a physical fight.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies based on trauma registry data are very rare in the Arabian Gulf region. A hospital-based retrospective study in Jordan demonstrated that violence (71%) was the most frequent cause of ED visits followed by road tra c injuries (23%) [17] Bala et al studied the prevalence of physical ghting and its associated factors among adolescent population in Qatar [18]. This study was based on a student health survey in school to determine the prevalence and factors associated with being engaged in a physical ght.…”
Section: Discussionmentioning
confidence: 99%